Collective Action in Lake Management (CALM): an Indonesian stocktake - Abdurrahim, A.Y.; Farida, F.; Sari, R.R.; Noordwijk, M. van; Yogaswarai, H.; Adiwibowo, S.; Dharmawan, A.H. (IOP Publishing, 2021)
More than 500 lakes in Indonesia have been recognized as important parts of local economies and, at least in some cases, identity, but there is little literature on resource management and collective action. By reviewing literature and using a 'serious game', this paper aims to (1) review some of the currently used generic frameworks for understanding collective action in natural resource management, (2) recount some experiences in supporting collective action in Lake Singkarak, Sumatra and (3) describe early steps in using 'serious games' developed elsewhere to increase stakeholder understanding of how upstream land management affects lake quality and functions. Some important findings are that collective action is an important key to sustainable natural resources management and the lake as a complex social-ecological system also requires collective action of multi-stakeholders from upstream to downstream. We recommend the use of DPSIR and Javanese 'gunungan' frameworks together with 'serious game' to identify socio-ecological problems and build multi-stakeholder collective action. Based on our initial research experience in Lake Singkarak, this combination of methods has succeeded in finding various problems, especially different types of knowledge, ways of knowing, and learning styles from multi-stakeholders. These problems are then used as a basis for finding and forming a common understanding which is then transformed into collective action in lake management.